Ecosystem approaches to fisheries a global perspective - Christensen, Villy; Maclean, J. L.; Pauly, D. (Cambridge University Press, 2011)
Inspired by the work of the renowned fisheries scientist Daniel Pauly, this book provides a detailed overview of ecosystem-based management of fisheries. It explores the complex and interdisciplinary nature of the subject by bringing together contributions from some of the world's leading fisheries scientists, managers and conservationists. Combining both research reviews and opinion pieces, and reflecting the breadth of Pauly's influence within the field, the book illustrates the range of issues associated with the implementation of the ecosystem approach and the challenge of long-term sustainability. Topics covered include global biodiversity, the impact of human actions on marine life, the implications for economic and social systems and the role of science in communicating and shaping ocean policy to preserve resources for the future. This book provides a complete and essential overview for advanced researchers and those just entering the field